ADVANTAGES OF USING THE MOODLE PLATFORM IN DISTANCE EDUCATION - Ergashevich Tangirov, Khurram; Abdurasulovna Abdullayeva, Makhliyo (Mental Enlightenment Scientific-Methodological Journal, 2024)
This article discusses the advantages and possibilities of using the Moodle platform in distance education and self-study. The creation of electronic information educational resources of an educational institution is not a purely technical issue, but for this it is required to use the scientific-methodical, organizational and pedagogical capabilities of the institution based on a systematic approach. Using Moodle, it is possible to organize distance courses with content such as text, supporting files, presentations, tests, practical tasks and surveys. The use of Moodle facilitates the educational process, easy creation of educational material, and also provides interactivity between the participants of the educational process. In this regard, the introduction of distance education technologies using information technologies in the educational process, in particular, the use of the Moodle platform in distance education, serves to increase the quality of education and independent education of students.